Dietary factors affecting entero-hepatic function of ruminants in the tropics - Abdullah, Abdul Salam; Rajion, Mohamed Ali (Elsevier Science B.V., 1998)
A lack of feed resources has been identified as the major constraint in ruminant livestock production in the tropics. Although forages, such as grasses, legumes and tree forages and the agro-industrial by-products, such as palm kernel cake, are available in abundance, their utilisation as animal feeds are limited due to the presence of dietary factors which may affect the voluntary intake and the entero-hepatic function of the animals. These dietary factors include saponins and copper in the palm kernel cake, mimosine and tannin in the tree legume (Leucaena leucocephala), sapogenins (epi-sarsasapogenin and epi-smilagenin) in the Signal grass (Brachiaria decumbens) and indospicine in the creeping indigo (Indigofera spicata). Great economic losses through general unthriftiness, poor weight gain, inefficient production and death have been attributed to these dietary factors.